External Debt Sustainability in HIPC Completion Point Countries - Sun, Yan (IMF Working Papers; Working Paper ;, 2004)
This paper examines a number of structural factors affecting the external debt sustainability of HIPC completion point countries. It shows that (i) while comparing favorably with other lowincome countries, the policy and institutional frameworks of completion point countries in general are still relatively weak, and their debt management practices remain inferior to international standards; and (ii) their export base remains narrow and fiscal revenue mobilization lags behind, even compared with many other low-income countries. Achieving and maintaining long-term debt sustainability in completion point countries will require continued structural reforms, timely donor support, and close monitoring of new borrowing in support of sound macroeconomic policies.